Kemampuan Stroke Literacy pada Perspektif Non Penderita Stroke: A Literature Review - Wenny Malisa; Mateus Sakundarno Adi (Jurnal Penelitian Kesehatan SUARA FORIKES, 2021)
Stroke is a non-communicable disease which is the second cause of disability and death globally. Stroke literacy is the ability to access, understand, assess, and apply information related to stroke to generate knowledge that enables a person to address the three domains of behavioral health prevention, treatment and care. Prevention of death and disability due to stroke can be developed by increasing literacy in people who are not sick. Data on stroke literacy among non-sufferers in the world is still lacking, the number of publications conducted in Indonesia is still very small and only focuses on sufferers. The research objective was to describe literacy skills from the perspective of nonsufferers. This study uses the literature review database method used, including Science Direct, Pubmed, BMJ, SAGE, Google Scholar, Google Scholar, Reserchgate and Biomed. In December 2020, 5 articles published in 2009 to 2019 were selected that met the inclusion criteria. The ability to easily access information is done by providing various choices of information sources, the ability to understand information related to stroke and symptoms is still low, the ability to assess information on people who have a low risk, and the ability to apply information by visiting health services when symptoms occur is still low. So it is hoped that health promotion efforts will increase the ability of the population to understand, understand, assess, and apply information related to stroke.Keywords: literacy stroke; the perspective of non sufferers; abilityABSTRAKStroke merupakan penyakit tidak menular yang menjadi penyebab kedua kecacatan dan kematian secara global. Stroke literacy adalah kemampuan mengakses, memahami, menilai, dan menerapkan informasi terkait stroke menghasilkan pengetahuan yang memungkinkan seseorang untuk mengarah ke tiga domain kesehatan perilaku pencegahan, pengobatan, dan perawatan. Pencegahan kematian dan kecacatan akibat stroke dapat dikembangkan dengan meningkatkan literasi pada orang yang tidak sakit. Data tentang stroke literacy pada non penderita di dunia masih sangat kurang, jumlah publikasi yang dilakukan di Indonesia masih sangat sedikit dan hanya fokus ke penderita. Tujuan penelitian untuk menggambarkan kemampuan stroke literacy pada perspektif non penderita. Penelitian ini menggunakan metode literature review database yang digunakan antara lain Science Direct, Pubmed, BMJ, SAGE, Google Scholar, Google Cendekia, Reserchgate dan Biomed pada bulan Desember 2020 terpilih 5 artikel yang dipublikasika pada tahun 2009 sampai 2019 yang memenuhi kriteria inklusi. Kemampuan mengakses informasi mudah dilakukan dengan tersedianya berbagai pilihan sumber informasi, kemampuan memahami informasi terkait stroke dan gejala masih rendah, kemampuan menilai informasi pada orang yang mempunyai faktor risiko masih rendah, dan kemampuan mengaplikasikan informasi dengan mendatangi pelayanan kesehatan saat terjadi gejala masih rendah. Sehingga diharapkan upaya promosi kesehatan untuk meningkatkan kemampuan populasi dalam mengakses, memahami, menilai, dan mengaplikasikan informasi terkait stroke.Kata kunci: stroke literacy; perspektif non penderita; kemampuan